AMATORIOS, ON WILD ASPHALT BY NELSON RODRIGUES - Nazário Silva Sávio, Elizandra (Revista Gênero e Interdisciplinaridade, 2023)
The desire to investigate the intrinsic relationships that involve human relationships, entangled by the fine line of erotic drive, and its consequences in traumatic memories, which involve us, in family and social contexts. The scrutinization of the formation of naked and buried fantasies, in the basements of female unconsciousness, which are exposed by Nelson Rodrigues in Asfalto Selvagem, Engraçadinha, his loves and his sins, represented in the characters Engraçadinha and Letícia, will be our purposes. We use explanatory methodology, with a qualitative approach